Design and Synthesis of Dy2TmSbO7/BiHoO3 Heterojunction: The Mechanism and Application for Photocatalytic Degradation of Sulphamethoxypyridazine - Jingfei Luan; Minghe Ma; Liang Hao; Hengchang Zeng; Anan Liu (Molecules, 2025)
A novel Z-scheme Dy2TmSbO7/BiHoO3 heterostructure photocatalyst was synthesized with the ultrasound-assisted solvothermal method. The Dy2TmSbO7/BiHoO3 heterojunction photocatalyst (DBHP) reflected wonderful separation efficiency of photogenerated electrons and photogenerated holes owing to the efficient direct Z-scheme heterojunction structure characteristic. The lattice parameter and the bandgap energy of the Dy2TmSbO7 were 10.52419 Å and 2.58 eV, simultaneously, the lattice parameter and the bandgap energy of the BiHoO3 were 5.42365 Å and 2.25 eV, additionally, the bandgap energy of the DBHP was 2.32 eV. Above results indicated that DBHP, Dy2TmSbO7 or BiHoO3 possessed an excellent ability for absorbing visible light energy, therefore, DBHP, Dy2TmSbO7 or BiHoO3 owned superior photocatalytic activity for degrading the sulphamethoxypyridazine (SMP) under visible light irradiation. The removal rate of the SMP after visible light irradiation of 135 min with the DBHP was 99.47% for degrading the SMP during the photocatalytic degradation (PADA) process, correspondingly, the removal rate of the total organic carbon (TOC) concentration after visible light irradiation of 135 min with the DBHP was 98.02% for degrading the SMP during the PADA process. The removal rate of the SMP after visible light irradiation of 135 min with the DBHP was 1.15 times, 1.29 times or 2.60 times that with Dy2TmSbO7, BiHoO3 or nitrogen-doped TiO2 (N-T). Therefore, the DBHP displayed higher photocatalytic activity for degrading the SMP under visible light irradiation compared with Dy2TmSbO7, BiHoO3 or N-T. Specifically, the mineralization rate for removing the TOC concentration during the PADA process of the SMP with the DBHP was 1.18 times, 1.32 times or 2.79 times that with Dy2TmSbO7, BiHoO3 or N-T. In addition, the stability and reusability of the DBHP were systematically evaluated, confirming that the DBHP owned potential applicability for degrading the antibiotic pollutant, which derived from the practical industrial wastewater. Trapping radicals experiments and the electron paramagnetic resonance measurement experiments were conducted for identifying the reactive radicals, such as the hydroxyl radicals (•OH), the superoxide anions (•O2−) and the photogenerated holes (h+), which were generated with the DBHP for degrading the SMP during the PADA process under visible light irradiation, as a result, the •O2− possessed the maximal oxidative capability compared with the •OH or the h+. Above results indicated the degradation mechanism and the degradation pathways which were related to the SMP. In conclusion, this study makes a significant contribution for the development of the efficient Z-scheme heterostructure photocatalysts and provides a key opinion to the development of the sustainable remediation method with the view of mitigating the antibiotic pollution.